(untitled) (CIPEEX, 2022)
The environmental crisis and social reproduction models do not prioritize the protection of biodiversity, causing a large portion of natural resources to reach a state of exhaustion. One of the alternatives to minimize the crisis is the creation of Conservation Units, which in turn are suitable places for the development of environmental education activities, a partnership that represents a two-way street that can benefit both parties.